Edukasi Rehabilitasi Bagi Masyarakat Melalui Media Flipchart di BNNP Provinsi Sumatera Selatan - Nebriska Ulfa Valonika; Rina Oktaviana (Yayasan Kawanad, 2026)
Drug abuse is a major problem that threatens public health, social well-being, and the sustainability of future generations. Its effects extend beyond physical health to psychological conditions, social relationships, and individual quality of life. Therefore, appropriate educational efforts are needed to improve public understanding of the importance of rehabilitation for people affected by drug use. This community service program provided education using flipchart media as a psychoeducational tool to present information in a systematic, communicative, and accessible manner. The implementation showed positive responses from the community, including greater attention, active participation, and increased understanding of drug rehabilitation services during the educational sessions. The use of visual information also helped clarify misconceptions about rehabilitation and encouraged a better understanding of rehabilitation as a medical and social recovery process. These findings indicate that flipchart media can support community education on drug rehabilitation and contribute to the dissemination of information related to rehabilitation services within families and communities.